StandOut 2.0 : - Buckingham, Marcus (Harvard Business Review Press, 2015)
That’s about to change. StandOut 2.0 is a revolutionary book and tool that enables you to identify your strengths, and those of your team, and act on them. The original edition of StandOut provided top-notch insights from one of the world’s foremost authorities on strengths, as well as access to a powerful, cutting-edge online assessment tool. StandOut 2.0 also includes the assessment and a robust report on your most dominant strengths. The report is easily exported so you can use it to present the very best of yourself to your team and your company.